Seasonal Change of Some Biochemical Parameters of Athletes Attending School Sports - Erdoğan, Ramazan (Progress in Nutrition, 2021)
Objective: Workouts affect the biochemistry of the organism significantly. Liver enzymes and lipids are important biochemical markers that affect the performance of athletes along with the training. The purpose of this study is to determine the effect of training sessions of athletes participating in school sports on liver enzymes and lipid metabolism during competitions. Method: The research group consists of 16 male volunteer athletes between 12-14 years of age. Athletes participating in the research trained for competitions according a program that lasts three months for 60 minutes per day three times in a week and one day for workouts in each week. Blood samples were taken twice before the school sports competitions started and at the end of the competitions. In the blood samples, liver enzyme values and lipid levels were determined. The data obtained were analyzed using SPSS 22 package program. Findings: In consequence of the analyzes, the differences in the levels of Aspartate aminotransferase (AST), Alanine aminotransferase (ALT), C-reactive protein (CRP) and Lactate dehydrogenase (LDH) were detected in the liver enzymes of the athletes participating in the study (p <0,05), whereas Gama-Glutamil Transferase (GGT), Alkaline Phosphatase, serum bilirubin total and bilirubin direct concentration levels were not statistically differentiated in the pre-posttest results (p> 0,05). A significant decrease was observed in the lipid values of the athletes in general as a result of the training performed and cholesterol, triglyceride, LDL and HDL values were found to differ significantly in the pre-post test results (p <0,05). Conclusion: As a result, it has been determined that long and regular training sessions have a positive effect on athlete’s liver enzyme levels and lipid metabolism. In this context, we think that performing performance measurements in athletes using physiological and biological parameters will positively affect the health and performance of athletes.